2018
DOI: 10.1002/2017jg004165
|View full text |Cite
|
Sign up to set email alerts
|

Biomodulation of Nitrogen Cycle in Suspended Sediment

Abstract: Biogeochemical experiments and modeling were coupled to investigate how nutrient leaching to aquatic ecosystems changes the dynamics of microbial community on suspended sediment and how these changes modulate the nitrogen cycle. Mineral suspensions amended with inorganic nitrogen (NH 4+ and NO 3−) and inoculated with native sedimentary microbial strains were tested in a settling column under continuous water quality measurements. Experiments were used to calibrate and validate a kinetic model that explicitly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 96 publications
1
6
0
Order By: Relevance
“…Time variations of measured dissolved inorganic nitrogen (DIN) concentrations for suspended sediment concentrations (a) 0.1, (b) 0.2, and (c) 0.4 g/L, respectively (Tang & Maggi, ). For each suspended sediment concentration, seven kaolinite samples are prepared: (i) nutrient‐free and biomass‐free (NFBF) and (ii–vii) nutrient‐affected and biomass‐free (NABF) and nutrient‐affected and biomass‐affected (NABA) with initial nutrients 1.5, 3.0, and 6.0 mM, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Time variations of measured dissolved inorganic nitrogen (DIN) concentrations for suspended sediment concentrations (a) 0.1, (b) 0.2, and (c) 0.4 g/L, respectively (Tang & Maggi, ). For each suspended sediment concentration, seven kaolinite samples are prepared: (i) nutrient‐free and biomass‐free (NFBF) and (ii–vii) nutrient‐affected and biomass‐free (NABF) and nutrient‐affected and biomass‐affected (NABA) with initial nutrients 1.5, 3.0, and 6.0 mM, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We would like to thank the three anonymous reviewers for their valuable comments that greatly contributed to improving this manuscript. We also acknowledge the raw data on water quality in all experiments, which was published as supporting information in Tang and Maggi (, https://doi.org/10.1002/2017JG004165) and can be downloaded online (from https://agupubs.onlinelibrary.wiley.com/action/downloadSupplement?doi=10.1002%2F2017JG004165&file=jgrg21007-sup-0003-supinfo.txt). This research was supported by the Open Research Fund of State Key Laboratory of Estuarine and Coastal Research of China (Grant SKLEC‐KF201811), the National Key R&D Program of China (Grant 2017YFC0405402), the National Natural Science Foundation of China (Grant 51339005), the Belt and Road Special Foundation of the State Key Laboratory of Hydrology‐Water Resources and Hydraulic Engineering of China (Grant 2018490911), and the Belgian Science Policy Office (BELSPO, Belgium) within the BRAIN.BE project INDI67 (Grant BR/143/A2/INDI67), and the JPI‐OCEANS Microplastics project WEATHER‐MIC (Grant BR/154/A1/WEATHER‐MIC).…”
Section: Acknowledgementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In lacustrine, riverine, and estuarine environments, both mineral and organic particulate matter and dissolved nutrients are deposited and accumulate to form mudflats . Nutrients can be adsorbed by the sediments and recycled through vegetation and microbial communities . Intensive studies have shown that successive flood/drain cycles, inherent to intertidal zones, can favor N 2 O release with the frequently changing aerobic/anaerobic status. , Recently, using a high-resolution map of NH 3 obtained from satellite observations, Van Damme et al also identified drying mudflats in the vicinity of Lake Natron in Tanzania as a previously unknown natural NH 3 source.…”
Section: Introductionmentioning
confidence: 99%